The Sinicization Path of English Loanwords in Social Media: A Case Study of Weibo - Harisa Ismi Dina; Yifan Hu (Universitas Negeri Surabaya, 2025)
This study takes the Weibo platform as a case to explore the Sinicization pathways of English loanwords in the context of social media. The core question addressed is: how do adaptation mechanisms of loanwords operate in this rapidly changing digital environment, and how does social media accelerate their localization? The study aims to reveal the influence mechanisms of social media on the dissemination and adaptation of loanwords and to analyze language innovation behaviors among young user groups. Employing a qualitative descriptive method, this research analyzes 150 English loanwords collected between October and December 2024. Based on Miao’s theory of loanword adaptation, the findings indicate that phonetic transcription (83 instances) is the most prevalent Sinicization strategy. Semantic transcription (32 instances) and hybrid loanwords (26 instances) reflect the unique characteristics of the Chinese character system. The study concludes that social media significantly accelerates the spread and localization of loanwords and highlights the leading role of young users in language evolution. This research provides valuable empirical insights for cross-cultural communication and language planning.